Exploring the relationship of triglyceride to high-density lipoprotein cholesterol and the triglyceride-glucose index with white matter hyperintensities in individuals with type 2 diabetes: a cross-sectional analysis - Pan, Jun; Zheng, Juan; Dong, Hua; Zhang, Haili; Hu, Zhiwei; Tang, Zhangchao; Xu, Hanwen (Frontiers in Endocrinology, 2025)
BackgroundPrevious studies have shown that the triglyceride-glucose index (TyG) is associated with white matter hyperintensities (WMH) in a healthy population, acting as a marker of insulin resistance (IR). Triglyceride to high-density lipoprotein cholesterol ratio (TG/HDL-c) has been also recognized as marker for IR. However, the connection between TyG or TG/HDL-c and WMH in type 2 diabetes mellitus (T2DM) patients is unclear. The aim of this study was to examine the link between TG/HDL-c or TyG and WMH in patients with T2DM.MethodsThe study enrolled a total of 420 T2DM patients. The WMH in baseline brain MRI scans was measured using the modified Fazekas scale. The relationship between WMH risk and severity in relation to TG/HDL-c and TyG was assessed through logistic and ordered logistic regression analyses. The variance inflation factor was employed to examine variable collinearity. Potential non-linear relationships between TG/HDL-c or TyG and the risk of WMH were examined using restricted cubic splines.ResultsThe median age of the study participants was 57.0 (18.0) years, 280 (66.7%) were men, and 263 (62.7%) were WMH-positive. The Fazekas score was correlated with the TG/HDL-c (r=0.366, P = 0.035) and TyG(r = 0.088, P = 0.025). Binary logistic regression analysis showed that TG/HDL-c (OR = 1.252, 95% CI 1.074-1.459) and TyG (OR = 1.883, 95% CI 1.359-2.609) were associated with the WMH. Multivariate adjusted restricted cubic spline plots showed a linear relationship between TG/HDL-c or TyG (P < 0.05, P-nonlinear > 0.05) and WMH. Multiple ordered logistic regression analyses showed that TG/HDL-c(OR = 1.123, 95% CI 1.028-1.226) and TyG (OR = 1.606, 95% CI 1.237-2.085) were independently associated with the burden of WMH. Subgroup analysis showed that TG/HDL-c were more substantially correlated with the WMH in male T2DM patients with a shorter duration of diabetes, younger age, lower blood pressure levels, and poor glycemic control (p<0.05). A comparable association of the TyG with WMH was also observed in these subgroups.ConclusionThe TyG and TG/HDL-c were independently and significantly associated with a higher prevalence and burden of WMH in patients with T2DM, which emphasizes the potential usefulness of these markers in early risk stratification.